Dynamic HTML : the definitive reference - Goodman, Danny (O'Reilly, 1998)
If you are a Web content developer these days, you have a lot of information to keep track of. You need to stay current on the relevant Web specifications, like HTML, CSS, DOM, and ECMAScript. You also need to know how the latest Web browsers from Netscape and Microsoft actually implement these standards, since browser implementations of the standards are less than perfect. Right now, you're forced to keep multiple reference books open on your desk (or multiple browser windows open on your screen), just to develop a simple dynamic Web page that works properly under both Navigator and Internet Explorer. Dynamic HTML: The Definitive Reference changes all that. This book is an indispensable compendium for Web content developers. It contains everything you need to create functional cross-platform Web applications, including: A complete reference for all of the HTML tags, CSS style attributes, browser document objects, and JavaScript objects supported by the various standards and the latest versions of Navigator and Internet Explorer. Browser compatibility is emphasized throughout; the reference pages clearly indicate browser support for every entity. Handy cross-reference indexes that make it easy to find interrelated HTML tags, style attributes, and document objects. An advanced introduction to creating dynamic Web content that addresses the cross-platform compromises inherent in Web page design today. If you have some experience with basic Web page creation, but are new to the world of dynamic content, Dynamic HTML: The Definitive Reference will jump-start your development efforts. If you are an experienced Web programmer, you'll find the browser-compatibility information invaluable. This book is the only DHTML reference that a Web developer needs. Dynamic HTML: The Definitive Reference is designed to work in conjunction with HTML: The Definitive Guide and JavaScript: The Definitive Guide . HTML: The Definitive Guide teaches you about every element of HTML in detail, with explanations of how each element works and how it interacts with other elements, as well as numerous examples. JavaScript: The Definitive Guide provides a thorough description of the JavaScript language, complete with sophisticated examples that show you how to handle common Web application tasks. Together, these three books provide a complete library for Web content developers.